Parenting scales : contributions to the factorial validity of the Portuguese version - Cruz, Orlanda (2011)
The purpose of this study is to confirm the structural validity of the Questioná- rio de Estilos Educativos Parentais (QEEP) in a sample of Portuguese adolescents. This instrument is an adaptation of the Parenting Scales to the Portuguese population and intends to evaluate adolescents’ perceptions of the rearing style of their parents. It is composed of 19 items related with two dimensions: Acceptance (Responsiveness) and Monitoring (Supervision). The sample has comprised 210 boys and 213 girls aged from 12 to 15 years. A two-dimensional model has emerged from confirmatory factorial analysis – Acceptance, similar to the original subscale, and Knowledge, composed by some items from the Monitoring dimension. Internal consistency coefficients are acceptable for research purposes.